THE CORPORATION STOCKHOLDER–ACCOUNTING'S FORGOTTEN MAN. - Greer, Howard C. (The Accounting Review, 1964)
Abstract In the article, the author focuses on stockholders, considered to be the minority group in business enterprises in the U.S. Stockholders are minor capitalists whose livelihood depends largely on the prudent and profitable investment of their limited savings. This group has now shrunk in numbers and diminished in importance. This group enjoys neither the security of a liberally-financed corporate pension plan, nor the beneficence of social-welfare hand-outs to the indigent. The author presents his thesis that the individual saver or the private accumulator of small amounts of capital is unduly disadvantaged by present-day conditions in the business sector. A stockholder faces a task of extraordinary difficulty in selecting and safeguarding his investments which stems from the neglect of his interests by those best situated to keep him properly informed namely, the independent accountants who certify to the financial statements of enterprises to which he commits his funds. For them, he is in truth the forgotten man.